Development Of Moral Reasoning Using Cognitive Behavioral Therapy - Siregar, Royhanun; Taufik, Agus; Yustiana, Yusi Riksa (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Adolescence is an important period in moral development and the search for self-identity. In adolescence is easily questioned by negative activities such as promiscuity, drug aid, student brawls, abortion, infidelity, rape, murder, and actions that unsettle the public including in criminal care. Violations committed by adolescents will prove moral values in a life together. Moral reasoning is a predictor of juvenile delinquency behavior, the lower the morale of adolescents, the higher the delinquency behavior. One of the efforts made to improve moral quality and inhibit the behavior of naughty adolescents (students) is to develop moral penalties by reorganizing cognitive or wrong ways of thinking that improve accordingly and minimize the behavior of juvenile delinquents that can be realized and counseling in schools with use cognitive behavioral therapy. Development of moral punishment by using cognitive behavioral therapy can restructure cognitive reasoning with everything related to morals, as well as doing good by the values of the norms adopted in the person and environment. The use of cognitive-behavioral therapy becomes a preventative and educative step for students in developing moral law to achieve the development of autonomous moral law